Masquerade - Burkhart, Jessica (Burkhart, Jessica. Canterwood Crest, 2012)
After winning a blue ribbon in her first show as a Canterwood Crest Academy student, Lauren and her friends begin planning a masquerade party to celebrate Halloween and Lauren's thirteenth birthday.